The effects of external and internal focus on the press behind neck lift among weightlifters - Ghazalli Ahmad Fazlan, Abdul Rani Mahamad Yusof, Low Jeffrey Fook Lee, (Universiti Pendidikan Sultan Idris, 2016)
The effects of external and internal focus on the press behind neck lift among weightlifters by Ghazalli Ahmad Fazlan, Abdul Rani Mahamad Yusof, Low Jeffrey Fook Lee,